Combined treatment of unresectable hilar cholangiocarcinoma with subsequent liver transplantation - D. A. Granov; I. I. Tileubergenov; V. N. Zhuikov; A. R. Sheraliev; A. A. Polikarpov; A. V. Moiseenko (Вестник трансплантологии и искусственных органов, 2022)
Objective: to demonstrate the experience of unresectable hilar cholangiocarcinoma treatment using neoadjuvant therapy followed by liver transplantation (LT).Materials and methods. From 2017 to 2021, six patients were included in the treatment protocol for unresectable Klatskin tumor followed by liver transplantation at Granov Russian Scientific Center for Radiology and Surgical Technology. The neoadjuvant therapy included endobiliary photodynamic therapy (PDT), as well as regional and systemic chemotherapy. Each method was used at least three times for 4 to 5 months with radiological evaluation and measurement of CA 19-9 levels. Patients were placed on the waiting list when the tumor marker reduced, or when there were no radiological signs of disease progression and there was no acute cholangitis. The recipients underwent laparoscopic abdominal revision for carcinomatosis and assessment of lymph nodes in the hepatoduodenal ligament with urgent morphological examination. Where there was no extrahepatic spread, LT was performed according to the classical technique with paracaval, para-aortic and hepatoduodenal lymphodissection, biliodigestive anastomosis by an isolated Roux loop of small intestine. The operation was performed in three patients, all of them were men aged 40 to 55 years (mean 48). The mean time from the start of treatment to transplantation was 9.3 months (range 6 to 14). Mean CA 19-9 level at the time of intervention was 81.3 IU/mL (8 to 212).Results. In three patients, CA 19-9 levels more than doubled on average over four months despite treatment. According to data from computed tomography RECIST assessment, two of the patients showed disease progression. In one patient, carcinomatosis was detected by diagnostic laparoscopy. In three patients, CA 19-9 levels decreased more than fourfold. Two of these patients were radiologically confirmed to have the disease stabilized, and one had a partial response. One patient died from sepsis three years after transplantation as a result of secondary biliary cirrhosis and biliary abscesses without signs of progression. Two patients are still alive after 6 and 21 months without signs of tumor progression.Conclusion. LT for unresectable Klatskin tumor is effective in controlling the bioactivity of the tumor through the use of neoadjuvant therapy